First person - Flanagan, Richard, 1961- (New York : Alfred A. Knopf, 2018)
"From the Man Booker Prize-winning author of The Narrow Road to the Deep North, the hypnotic tale of a ghost writer writing the memoir of a notorious con man, and the chilling events that unfold as their lives become increasingly intertwined. Kif Kehlmann, a young, penniless writer, is rung in the middle of the night by the notorious con man and corporate criminal, Siegfried Heidl. About to go to trial for defrauding the banks of $700 million, Heidl offers Kehlmann the job of ghost-writing his memoir. He has six weeks to write the book, for which he'll be paid $10,000. But as the writing gets under way, Kehlmann begins to fear that he is being corrupted by Heidl. As the deadline draws closer, he becomes ever more unsure if he is ghost writing a memoir, or if Heidl is rewriting him--his life, his future. Everything that was certain grows uncertain as he begins to wonder: who is Siegfried Heidl--and who is Kif Kehlmann? As time runs out, as Kehlmann's world feels it is hurtling towards a catharsis, one question looms above all others: what is the truth? By turns compelling, comic, and chilling, this is a haunting journey into the heart of our age"--
"This is a Borzoi book."